Industrial Development and Irish National Identity, 1922-1939 - Daly, Mary (Syracuse University Press, 1992)
Based on extensive research for the Holland Land Company Papers in Amsterdam's City Archives, Professor Chazanof's study presents a previously unexplored part of the political history of New York State on regional, national, and international levels.